The complex clause in boruca (2010)
This paper describes the complex clause in Boruca, a Chibchan language once spoken in the southern territories on the Pacific coast of Costa Rica. The present study concentrates on the behavior of complex clauses, following a major distinction between paratactic and hypotactic constructions. Paratactic constructions are divided into asyndetic and syndetic constructions. The latter are quite frequent and it is common to find the syndetons: mang, ní, ihchí and iné in the combination of sentences in regular speech. Hypotactic constructions also have asyndetic and syndetic constructions usually functioning as object complements. There is also evidence for reported speech, indirect questions and adverbial clauses (classified at least into seven different types).